Dualitas Strukturasi Giddens : Risiko Politik Investasi Pemindahan Ibu Kota Negara - Niken Eriana Azzahra Fauzi; Shalvena Aura Azzura; Khoirun Nisa (Universitas Maritim AMNI Semarang, 2023)
The Power of the State Apparatus As a government institution in the perspective of moving the State Capital becomes part of the practice of social reproduction. Various considerations wrapped in political consensus are a challenge for bureaucrats. It is suspected that his involvement in carrying out his duties and responsibilities simultaneously has an impact on the domino effect that arises as a response to transcendental transformation. The grand factor driving the transfer of IKN is such as population agglomeration on the island of Java, which has an impact on economic stagnation which is increasingly apprehensive. In other words, the underdevelopment experienced by regions outside Java will soon be resolved. The symptom of duality in the structuring of agent behavior becomes so essential considering that the agent, namely the bureaucrat, is the key person as well as a vessel for social reproduction. Thus, it is hoped that Giddens' conception in the corridor of internal bureaucratic structuring in the search for resources as a nation accelerator can be realized properly. This is in line with the transformation of community development which requires institutional elements to accommodate all levels of stakeholders. Giddens' concept emphasizes how patterns of power relations, systems and structures unite in building the evolution of a theologically patterned society. The duality approach between the possessors of power and their powers will influence each other on an ongoing basis. More than that, the connection between political phenomena in creating opportunities will be very radical when an actor expects to optimize the capacity of his actions to influence other elements. Various speculations from minority groups to the voice of environmental elements over the transfer of the national capital are purely based on an oligarchic profit-sharing project. This skeptical assumption overshadows the fact that the development transformation synergy is fraught with risks for the possibilities that will occur. Especially regarding investment-motivated funding for the state capital project, it will confront the role of bureaucrats in a metaphorical setting in the growth of national economic capacity. It is claimed that the megaproject will participate in mobilizing supporting resources that cannot be separated from the comparison of science and technology development.